434 Measurement instruments for integration within children and young people healthcare systems and networks: a rapid review. (17th August 2022) - Dedat, Zainab; Hope, Steven; Summerbell, Carolyn; Viner, Russell; Hargreaves, Dougal; Nicholls, Dasha; Scott, Steph; Hillier-Brown, Frances
Abstract : Aims: Measuring integration is essential to effectively improving the development, design and implementation of healthcare systems and networks. This review aims to identify measurement instruments for integration within children and young people healthcare systems and networks. Methods: We conducted a rapid review following the guidance from Cochrane Rapid Reviews Methods Group. The review was registered with the PROSPERO registry of systematic reviews (registration number CRD42021235383). We searched electronic databases (PubMED and Embase) in January 2021 using three main concepts: '(integrated care) AND (child population) AND (measurement)'. Additionally, grey literature was searched through the database Open Grey, alongside google searches using keywords. Reference lists of all included studies and related systematic reviews were checked for additional studies. Title, abstract and full-text screening, and data extraction was conducted by one reviewer and checked by a senior reviewer. Results: Following screening of 2147 articles, 20 articles describing 19 measurement instruments, were eligible for inclusion. Fourteen of the 20 articles were conducted in the USA, two in Netherlands, two in Canada, one in Brazil and one in Germany and all the studies were published post-2000. There was a diversity of health conditions included in the studies: six measured integration within systems designed for children with medical complexity, four within systems for any health condition, two for special health needs, two for mental health, and six for other health conditions (ADHD, behavioural health needs, cerebral palsy, children with disabilities, chronic conditions, and linguistic and developmental disorders). Across children and young people healthcare systems and networks, there was no unified measurement instrument of integration. The most frequent type of assessment used to measure integration was a questionnaire (16 identified), but interviews, patient data and healthcare records, digital technology and focus groups were also used. The most frequent integration outcome assessed was quality of care coordination (measured by seven instruments). The remaining integration outcomes assessed were: quality of collaboration (five instruments), continuity of care (three instruments), completeness of care (two instruments), and care-coordination usage, structure of care, use of technology in care and quality of communication (each measured by one instrument, respectively). Conclusion: This review found there are a variety of measurement instruments for integration within children and young people healthcare systems and networks. Further research is needed on how best to standardise the measurement of integration within these systems. Furthermore, future work could also focus on the validation and reliability of the already existing measurement tools across different contexts, alongside the investigation of new tools being developed and used. This rapid review is part of a wider project investigating integrated care systems for children and young people funded by the NIHR School for Public Health Research (https://sphr.nihr.ac.uk/research/child-health-system-evaluation-project-integrated-care-systems-and-sustainability-and-transformation-partnerships/).